Evaluasi Optimasi Alat Gali Muat Dan Alat Angkut Terhadap Produksi Batu Kapur Menggunakan Metode Match Factor, Fishbone dan LinearProgramming Simplex pada Blok Pendapatan Negara Bukan Pajak (PNBP) dan Pit Limit Barat (PLB) Bukit Karang Putih PT. Semen Padang - Naya Makaristi Andrea; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2021)
In the implementation of limestone mining of non-tax state revenue blocks (PNBP) and west pit limit blocks (PLB) at PT Semen Padang,the company uses 1 Hitachi EX-2500 (EH 6) excavator and 5 Komatsu 785-7 HD dump trucks on the former blocks, and 1 Catterpillar 6030 (EC 3) Excavator and 3 HD 785-7/777 D dump trucks for the latter blocks. The average actual productivity in October 2020 in the PNBP block for 1 unit of the EH 6 excavator was 1,086.85 tons per hour and 5 units of HD 785-7 dump trucks of 643.76 tons per hour, while the average actual productivity in the PLB block for 1 unit of excavator EC 3 amounting to 1,324.65 tons per hour and 3 units of dump truck HD 785-5/777 D amounting to 1,184.83 tons per hour. Both have not reached the target of 1200 tons per hour. This is due to the mismatch of digging and transportation equipment, the large distribution time for each dump truck, standby hours and breakdown resulting in less working time as planned.Efforts made as an evaluation of the mismatch optimization of excavators and conveyances use the Match Factor method. The amount of dump truck circulation times, standby hours and breakdowns were done by looking at the root causes of the Fishbone diagram. To achieve optimal production results with minimal costs, the Linear Programming Simplex analysis method was used as an improvised solution in this study.The results of this study are based on the actual conditions, the amount of production in the PNBP and PLB blocks for 1 month was 1,027,391.00 ton, based on the evaluation with the Match Factor method, the amount of production was obtained as much of 1,308,072.54 tons, based on the evaluation with the Fishbone method, the total production was 1,164,531.38 tons, and based on the application of the analysis of the Linear Programming Simplex method, the amount of production was 1,237,902.15 tons. As the most optimal solution to be applied in achieving the limestone production target in October 2020, which is 973,989 tonnes, the Fishbone and Linear Programming Simplex method can be used because it reaches the most optimal amount of production in 1 month, which is 1,404,012.58Ton.  Keywords: Productivity, Excavator, Dump Truck, Match Factor, Fishbone, Linear Programming Simplex